Revisiting potential output in Denmark - Troels Kromand Danielsen; Casper Winther Nguyen Jørgensen; Rasmus Mose Jensen (Danmarks Nationalbank, 2017)
This paper provides a detailed description of Danmarks Nationalbank's current methodology for estimating potential output and output gaps in the Danish economy. Although the general framework is similar to the previous production function approach in Andersen and Rasmussen (2011), each of the individual sub-models for the participation rate, unemployment and total factor productivity have been revised. First, the new approach to modelling the structural participation rate explicitly incorporates demographic variation across age groups, student propensity and a discouraged worker effect. Second, the estimation of structural unemployment now uses a wage Phillips curve rather than the wage share, since the latter is prone to substantial data revisions. Finally, an unobserved components model based on the degree of spare capacity in manufacturing is formulated for the total factor productivity (TFP) gap, thereby replacing the former extended HP filter. The results suggest that the Danish economy is operating very close to its cyclically neutral capacity in 2016. The overall view on the output gap is thus unchanged. – – Dette arbejdspapir giver en detaljeret beskrivelse af Danmarks Nationalbanks nuværende metode til at estimere potentiel produktion og produktionsgabet for dansk økonomi. Det overordnede metodeapparat svarer til den tidligere produktionsfunktionstilgang i Andersen og Rasmussen (2011), men de enkelte delmodeller for erhvervsfrekvens, ledighed og totalfaktorproduktivitet er revideret. For det første så indarbejder den nye modellering af den strukturelle erhvervsfrekvens eksplit demografi på tværs af aldersgrupper, studietilbøjelighed og en "discouraged worker" effekt. For det andet så anvendes der nu en løn-Phillips-kurve i estimationen af den strukturelle ledighed i stedet for lønkvoten, da sidstnævnte lejlighedsvis revideres betydeligt. Endelig opstilles en unobserved components model for TFP-gabet, som erstatter det tidligere udvidede HP-filter. I modellen anvendes den ledige kapacitet i industrien fortsat som indikator for cykliske udsving i TFP. Resultaterne peger på, at danske økonomi opererer meget tæt på sit konjunkturneutrale niveau i 2016. Den overordnede opfattelse af produktionsgabet er således uændret.
Keywords: 330